2016
DOI: 10.1002/anie.201601303
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Di‐peri‐dinaphthoporphyrins by PtCl2‐Mediated Cyclization of Quinodimethane‐type Porphyrins

Abstract: Di-peri-dinaphthoporphyrins can be regarded as a key and common substructure of fused porphyrinoids. PtCl2 -mediated cycloisomerization reaction of quinodimethane-type porphyrins provided these doubly fused porphyrins, which exhibit characteristic paratropic ring currents that presumably arise from 24π antiaromatic circuit as a dominant resonance contributor. UV/Vis absorption spectra, cyclic voltammetry, and excited-state dynamics as well as theoretical calculation support this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…Osuka et al also reported the similar peri -dinaphthoporphyrin 94 , 77 which comprises a partial structure of 91 and porphyrin tapes. 78 94 was characterized as a closed-shell anti-aromatic molecule ( Fig.…”
Section: Kekulé/non-kekulé Radicalsmentioning
confidence: 88%
“…Osuka et al also reported the similar peri -dinaphthoporphyrin 94 , 77 which comprises a partial structure of 91 and porphyrin tapes. 78 94 was characterized as a closed-shell anti-aromatic molecule ( Fig.…”
Section: Kekulé/non-kekulé Radicalsmentioning
confidence: 88%
“…The two stacked molecules are horizontally slipped with an offset distance of 2.664 Å [11b]. A similar dimeric stacking was also seen in the solid-state of 4Ni, and the interplane distance and the slip-stack offset distances were 3.455 and 2.813 Å, respectively [7]. Though the crystal packing force should be considered, the shorter packing distance in 5Ni implies a more facile p-stacking nature between two antiaromatic molecules due to less steric bulkiness of the peripheral alkyl groups.…”
Section: Resultsmentioning
confidence: 81%
“…5Ni displayed split first oxidation waves at 0.17 and 0.38 V and an additional wave at 0.82 V. 5Ni also showed two reversible reduction waves at -1.08 and -1.71 V. These peaks are negatively shifted as compared with those of 4Ni, and the relatively larger negative shifts in the reduction waves of 5Ni are consistent with the MO energy calculations. Notably, 4Ni also showed split oxidation waves at 0.31 and 0.38 V, and these two peaks likely correspond to each 0.5 electron oxidation process as compared with other peaks [7]. The differences between the first and second oxidation potentials (DE ox ) are 0.07 V for 4Ni and 0.21 V for 5Ni.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations